PSYCHOLOGICAL SERVICE – AS AN INTEGRAL PART OF THE EDUCATION SYSTEM - Talipova Feruza (Modern American Journals, 2025)
In the article, the author explained that the organization of a psychological service in higher educational institutions is the need of the time, and focused on the tasks of the psychological service.
Keywords: Higher education, psychological service, teachers, psychological knowledge.